First observation of ion beam channeling in bent crystals at multi-TeV energies - S. Redaelli; M. Butcher; C. Barreto; R. Losito; A. Masi; D. Mirarchi; S. Montesano; R. Rossi; W. Scandale; P. Serrano Galvez; G. Valentino; F. Galluccio (European Physical Journal C: Particles and Fields, 2021)
Abstract Planar channeling in bent crystals has been observed in LHC with multi-TeV proton beam in 2015. Two crystals, mounted on novel high-accuracy goniometers (one in the horizontal and one in the vertical plane), are integrated in the LHC collimation system, for studying the feasibility of the crystal-based collimation scheme. Using this experimental setup, tests with fully-stripped lead ion beams at both 450 Z and 6500 Z GeV were carried during dedicated LHC beam time. Planar channeling was observed for the first time with lead ions at these unprecedented energies surpassing by more than 1 order of magnitude the previous state-of-the-art for lead heavy ions and providing an important experimental basis for future applications of bent crystals in beam manipulations. The set of measurements performed to confirm this observation, as the local loss reduction in presence of channeling and the evidence of a deflected beam downstream of the crystal, are presented.